The Use of Assemblr edu as an Interactive Learning Medium to Improve Mathematical Critical Thinking Skills - Afifah Ainun Nadjla; Deasy Wahyuni (Proceeding International Conference on Mathematics and Learning Research, 2025)
Critical thinking skills are essential competencies in 21st-century mathematics education, requiring students to analyze, evaluate, and reflect on concepts deeply. However, the abstract and symbolic nature of mathematics often hinders students' conceptual understanding. Augmented Reality (AR) provides an innovative approach by integrating threedimensional digital objects into real-world environments, allowing interactive exploration of mathematical ideas. This study examines the effectiveness of Assemblr Edu, an AR-based learning medium, in enhancing students' mathematical critical thinking skills. Employing a quasi-experimental pretest–posttest control group design, the study involved 60 secondary students divided into experimental and control groups. A validated mathematical critical thinking test was used, and data were analyzed through Analysis of Covariance (ANCOVA) with pretest scores as covariates. The findings revealed a significant difference between groups F(1.57)= 37.93,p < 0.001, n2 = 0.399. The experimental group's mean improvement was +23.74 points N-Gain = 0.59, high category), while the control group's improvement was +10.21 points(N-Gain = 0.25, medium category). The 3D interactivity of Assemblr Edu effectively fostered clarification, analysis, and logical reflection, confirming its role in promoting higher-order thinking skills aligned with the critical reasoning dimension of Indonesia's Merdeka Curriculum.